2007
DOI: 10.1177/030089160709300111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Symptom-To-Treatment Interval on Prognosis in Lung Cancer

Abstract: The shorter the diagnostic interval, the shorter was the median survival in our study. The reason for the apparent discrepancy between poor prognosis of lung cancer patients in spite of early diagnosis might be much faster progression of the disease itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 28 publications
7
46
1
1
Order By: Relevance
“…However, contrary to expectation, timely care was not associated with better prognosis in these patients. Although this result corroborates findings from previous studies, [35][36][37] it contradicts findings from 2 US studies. 38,39 The observed paradoxical results may be explained by selection bias, as symptomatic patients with advanced stage disease are more likely to receive prompt (timely) care, despite their poor prognosis to begin with.…”
Section: Discussionsupporting
confidence: 85%
“…However, contrary to expectation, timely care was not associated with better prognosis in these patients. Although this result corroborates findings from previous studies, [35][36][37] it contradicts findings from 2 US studies. 38,39 The observed paradoxical results may be explained by selection bias, as symptomatic patients with advanced stage disease are more likely to receive prompt (timely) care, despite their poor prognosis to begin with.…”
Section: Discussionsupporting
confidence: 85%
“…Two Scandinavian studies conducted revealed that the lag between the initial visit to the GP and diagnosis confirmation among patients with lung cancer was 88 and 97 days, respectively (20,21). While most studies found a delay relatively longer than what we have identified, a Turkish study reported that the average delay in a diagnosis for lung cancer was just 41 days (18). Because the countries that have been investigated are very distinct not only in their healthcare systems, but also very much in their cultural and local contexts, we believe further examination into their health service delivery and healthcare-seeking behavior is worthwhile.…”
Section: Discussionmentioning
confidence: 52%
“…This is despite clear advice in the British National Institute for Clinical Excellence (NICE) guidelines regarding chest x-ray referral 42 . The delay from first presentation to referral to a respiratory specialist has been reported to range from a mean of 34 days 38 to 73 days (range 0->175) 37,36,39,43,44 .…”
Section: Symptom Recognition and Reportingmentioning
confidence: 99%